The Prevalence of Endemic Goiter and Its Relationship to Urine Iodine in Primary School Age Children in Khoramabad - mahnaz mardani; Fateme gholaami; pouria rezapour; farzad ebrahimzadeh (Shiraz University of Medical Sciences, 2015)
Backgrounds: Iodine deficiency disorder is a major public health problem in areas where there is a lack of iodine in drinking water, soil, and food. This study was carried out to assess the prevalence of goiter among school children in the age group of 6-10 years in Khorramabad city. Also, the level of urine iodine was evaluated. Methods: The study was conducted from January 2012 to January 2013 in 1125 school children of 6-10 years of age, attending all the schools of Khorramabad city. The subjects were selected through stratified, random, and cluster sampling methods. Their Goiter degrees were evaluated according to WHO classification. Excretory urine iodine was measured based on micrograms per deciliter. Furthermore, the digestion method was used for experimentation. Results: Out of the 1125 subjects, 866 (77%) had Goiter. 24.2% were diagnosed with Goiter 1a, 45.3% with goiter 1b, and 7.2% with type 2 Goiter. Regarding Goiter, there was no difference between the two sexes. The prevalence of goiter increased with age, but it decreased with the increase of parental educational level. Also, goiter prevalence was lower in families with a higher socioeconomic status. The median urinary iodine was 17.1 micrograms per deciliter, which is desirable in terms of the WHO criterion. Conclusion: The results of the study indicated that using iodizing edible salt to fight with iodine deficiency was effective and helped Khorramabad reach the International indexes of iodine control. Despite this, Khorramabad is one of the hyper- endemic regions in the world.